Using composable NFTs and blockchain for the creation of EV battery digital passports with sustainability and traceability features - Haya R. Hasan; Khaled Salah; Ahmad Mayyas; Ahmad Musamih; Ibrar Yaqoob; Mohammed Omar; Raja Jayaraman (Sustainable Futures, 2025)
Greenhouse gas emissions and carbon footprints have surged dramatically, with the transportation industry being a major contributor. While the UN aims to adopt zero-emission vehicles by 2040, the demand for electric vehicles (EVs) raises sustainability concerns about sourcing earth metals for batteries. Digital passports have emerged to track a product’s lifecycle, composition, certifications, origin, and recyclability. However, existing EV battery passport systems lack sufficient traceability, immutability, auditability, and are prone to manipulation due to their centralized nature. In this paper, we propose a decentralized blockchain-based digital passport for EV batteries using composable Non-Fungible Tokens (NFTs) to ensure traceable, tamper-proof records that promote transparency across the supply chain. Our solution enables standardized data sharing and interoperability while integrating off-chain storage for efficiency. We evaluate four cathode chemistries using ten sustainability Key Performance Indicators (KPIs) to compute an overall sustainability score per battery. We present a system architecture, smart contracts, and supporting algorithms are presented, with testing and validation in a simulated environment. A cost and security analysis confirms affordability and resilience against known attacks. Our approach offers practical value for sustainability assessments, regulatory audits, carbon footprint tracking, and circular economy initiatives by providing immutable, component-level provenance and real-time KPI updates. Limitations include simulation-based validation, lack of stakeholder testing, and scalability challenges in live deployments. While we address some of these, via Layer 2 scaling and modular smart contract design, further research is required to validate adoption in real-world EV supply chains. The smart contract code is made publicly available on GitHub.